Exploring the single parenting process in Malaysia: issues and coping strategies - Abd Hamid, Siti Rafiah; Salleh, Sakinah (2018)
Parents play significant roles in shaping their children’s lives and developments. They are role-models for their children. Being a single parent, parenting issue, financial constraints, family well-being, and children’s education are interwoven issues found among single parent. Being a single parent, they are the sole breadwinner for their family. To some extent a single parent has to do double jobs to support their family and this give rise to other related social and psychological issues. Findings from studies indicated that children from this family model experienced depression and emotional distress. They were frequently found highly at-risk in terms of being potential school drop-outs, substance abuser, neglected, some were sexually active and end up in teen pregnancy. Effective time management is also another depressing issue and time management requires creativity. Findings from studies on single parenting dynamic indicated that lacking of physical, mental and emotional preparedness would result in collapse of the family structure. In Malaysia, single parenting encounters similar experiences. However, an in-depth study on single parenting issues is necessary as this helps to validate their experiences and the findings would add to the current body of knowledge. It is the intent of this study to explore the Malay single parenting process, parenting issues and challenges, and their coping mechanisms among Malaysian subjects. This study is guided by the ecological systems theory. The theories helped the researchers in terms of understanding single parenthood problems. The qualitative case study was employed via the use of interview protocol which employed open-ended questions to explore single parenting process and examine single parenting issues and challenges and as well as to identify their coping strategies. Thematic analysis was employed to analyze the data. The participants were single Malay working women who were either widowed or divorced. Major findings highlighted single parenting intricacies which include; i) parent’s psychological well-being issues, ii) difficulties related to single parenting process, iii) work-family conflicts, iv) financial constraints. This study implicates several stakeholders namely family practitioners, single parent, social welfare agencies, policy makers, both government and non-governmental bodies (NGOs), religious institutions, school counselors and teachers. They are the internal and external support system needed badly by the single parents in assisting them towards the process of improving their socio-economic status, assist them in their child upbringing process and as well as improve the family economic per capita. Assistances and interventions by these quarters were found necessary and pertinent for the families’ future direction and sustainability.